Problematika Fundraising Di LAZISNU Kudus - Naim, Abdul Haris (UIN Sunan Kudus, 2018)
Fundraising zakat activities is a necessity. Lazisnu Kudus is a district-level non-profit organization that is devoted to community empowerment through productive utilization of zakat, infaq, sadaqah funds and other generous funds from individuals, institutions, companies and other agencies. Based on that, the researcher feels it is important to conduct research on Fundraising Lazisnu Kudus roblems related to the problems in applying Fundraising.From the results of the research that has been parsed in the previous chapter and the analysis that has been carried out, conclusions can be taken as follows: 1. Fundraising Strategy in Lazisnu Kudus. Lazisnu Kudus has successfully carried out fundraising activities with various strategies. 2. The inhibiting factor of fundraising activities in Lazisnu a. Institutional obstacles. That is the opinion of the advisory board stating that the management and employees of Lazis are amil, so they are not entitled to get the zakat portion. b. Fundraising inhibiting factors, which are direct inhibitors: that is, when direct donors are rejected, and donors permit to donate. And indirectly inhibiting: when conducting fundraising activities, namely fanaticism donors to other ormas, donors did not know the Lazisnu office 3. Supporting Factors from Fundraising Activities in Lazisnu Kudus. Supporting fundraising activities in Lazisnu is to use more toolmarketing when taking, there are targets and evaluations and rewards given. This can trigger enthusiasm to continue to do fundraising properly so that the funds can be raised.